"Sweet tooth"-oriented SN38 prodrug delivery nanoplatform for targeted gastric cancer therapy. Issue 12 (10th March 2021) - Ding, Ning; Xu, Shengjun; Zheng, Sheng; Ye, Qianwei; Xu, Li; Ling, Sunbin; Xie, Shanshan; Chen, Wenwen; Zhang, Zizhen; Xue, Meng; Lin, Zhenghua; Xu, Xiao; et al.
Abstract : Motivated by the overexpression of GLUT1 in gastric cancer, a targeted SN38 prodrug delivery nanoplatform was constructed and exhibited potent antitumor efficiency, which brought a new insight to the design of nanomedicine against cancer. Abstract : Most cancer cells employ overexpression of glucose transports (GLUTs) to satisfy glucose demand ("Sweet Tooth") for increased aerobic glycolysis rates. GLUT1, one of the most widely expressed GLUTs in numerous cancers, was identified as a prognosis-related biomarker of gastric cancer via tissue array analysis. Herein, a "Sweet Tooth"-oriented SN38 prodrug delivery nanoplatform (Glu-SNP) was developed for targeted gastric cancer therapy. For this purpose, a SN38-derived prodrug (PLA-SN38) was synthesized by tethering 7-ethyl-10-hydroxycamptothecin (SN38) to biocompatible polylactic acid (PLA) with the appropriate degree of polymerization ( n = 44). The PLA-SN38 conjugate was further assembled with glycosylated amphiphilic lipid to obtain glucosamine-decorated nanoparticles (Glu-SNP). Glu-SNP exhibited potent antitumor efficiency both in vitro and in vivo through enhanced cancer cell-specific targeting associated with the overexpression of GLUT1, which provides a promising approach for gastric cancer therapy.